(untitled) (Baghdad Science Journal, 2025)
A series of new compounds including p-bromo methyl pheno acetate [2]. N-( aminocarbonyl)–p-bromo pheno acetamide [3] , N-( aminothioyl) -p-bromo phenoacetyl amide [4], N-[4-(p-di phenyl)-1,3-oxazol-2-yl]-p-bromopheno acetamide [5],N-[4-p-di phenyl]-1,3-thiazol-2-yl-p-bromo phenoacet amide [6], p-bromopheno acetic acid hydrazide [7] , 1-N-(p-bromo pheno acetyl)-1,2-dihydro-pyridazin-3,6- dione [8], 1-N-(p-bromo pheno acetyl)-1,2-dihydro-phthalazin-3,8- dione[ 9], 1-(p-bromo pheno acetyl)-3-methylpyrazol-5-one [10] and 1-(p-bromo phenol acetyl)- 3,5-dimethyl pyrazole [11] have been synthesized. The prepared compounds were characterized by m.p.,FT-IR and 1H-NMR spectroscopy. Also ,the biological activity was evaluated .